A resting-state fMRI study on early-stage drug-naïve Parkinson's disease patients with drooling. (10th November 2016) - Hou, Yanbing; Luo, Chunyan; Yang, Jing; Song, Wei; Ou, Ruwei; Liu, Wanglin; Gong, Qiyong; Shang, Huifang
Highlights: Drooling is a common symptom in PD patients. Drug-naïve PD patients are critical to reflect primary pathophysiologic changes. There is a decreased FC in cortico-striatal networks in PD patients with drooling. It might promote understanding of neural system effects resulting from drooling. Abstract: Objective: Drooling is a common symptom in Parkinson's disease (PD). This study used resting-state functional MRI (fMRI) to evaluate the brain connectivity of cortico-striatal circuits in PD patients with drooling. Method: We enrolled 30 early-stage drug-naïve PD patients and 30 matched normal controls. Among the PD patients, 15 patients were classified as "droolers" with the presence of drooling and 15 patients as "non-droolers" with the absence of drooling. All participants underwent resting-state fMRI scans on a 3-T MR system, focusing on the functional connectivity of striatum subregions. Results: Compared with PD patients without drooling, PD patients with drooling showed the significantly reduced functional connectivity of putamen within bilateral sensorimotor cortices, superior and inferior parietal lobules and areas in the right occipital and temporal lobes. No increased functional connectivity was found between the two PD subgroups. In addition, compared with healthy controls, both PD subgroups showed the functional connectivity alterations in cortico-striatal loops. The decreased functional connectivity was prominent in the most affected posterior putamen, and the increased functional connectivity was evident only in the relatively unaffected anterior striatum and caudate. Conclusion: By studying a cohort of early-stage drug-naïve PD patients, we eliminated the potential confounding effects of antiparkinson medication on the functional integration of neural networks. We demonstrated decreased connectivity within cortico-striatal networks in PD patients with drooling. These findings might be helpful for promoting the further understanding of neural system effects underlying drooling in PD. Our result is preliminary and further investigation is needed.